Development of Solar Bubble Dryer Mark II for rice - CGIAR Research Program on Rice (2021)
Continuous improvement of the technology was done on Version 1. Slowing down sales of Version 1 due to COVID and other factors led to stocks of components for Version 1 still being available. Mark 2 is expected when stocks are consumed.